USE OF 3D MODELING AND QUICK PROTOTYPING IN TEACHING INTERIOR DESIGN - Yeremenko, Liudmyla Karpivna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
The article highlights the specifics of teaching the subject of interior design in distance learning and design, describes the main methods of teaching the discipline "Layout and modeling in the material" and the impact on its teaching of modern technologies.